THEORY AND PRACTICE OF PROGRAMMING ON THE NEUROPEDAGOGICAL BASIS OF LINGUISTICS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article is the result of scientific research in the field of neuropedagogy and neuropsychology, the study of pedagogical and psychological processes from the point of view of neurological changes occurring in the human brain, that is, the synergism of neurology with pedagogy and psychology - in 1997 as a separate discipline ideas about neurolinguistic programming and its practice, which emerged as a result of the emergence and further formation of knowledge related to the educational process of the individual, subject and person, are presented.